KONTEKSTUALITAS AFFIRMATIVE ACTION DALAM KEBIJAKAN PERTANAHAN DI YOGYAKARTA - Widhiana Hestining Puri (BHUMI: Jurnal Agraria dan Pertanahan, 2013)
The land policy in Yogyakarta Special Province, especially the one related to land ownership by the Indonesian-Chinese blood, is different from that of another region. It is stated on the Governor’s Instruction No. K. 898/I/A/1975 aboutThe Uniformity of Giving the Right on Land Policy to Non Indonesian citizens, Indonesian-Chinese blood which states that theyare not allowed to own the land. The policy is called the affirmative action that is the positive discrimination having theideological purpose of reaching the justice and similarity for The Indonesian origins in Yogyakarta. The affirmative action needssome requirements to get the effective implementation.Keywords: Affirmative action, land policy, Yogyakarta